2001
DOI: 10.1046/j.1464-5491.2001.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved glycaemic control by addition of glimepiride to metformin monotherapy in Type 2 diabetic patients

Abstract: Addition of glimepiride to metformin in Type 2 diabetic patients inadequately controlled by metformin alone resulted in superior glycaemic control compared with glimepiride or metformin monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
65
0
14

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 21 publications
(21 reference statements)
13
65
0
14
Order By: Relevance
“…This coincides with a study conducted by Charpentier et al, Wang et al, and Pareek et al, [13][14][15] who showed a significant reduction in FBS and PPBS (P < 0.001) from baseline than either glimepiride or metformin alone. The results of the present study coincide with these studies where FBS and PPBS decreased significantly (P < 0.01) from baseline to 12 weeks (P < 0.001).…”
Section: Discussionsupporting
confidence: 71%
“…This coincides with a study conducted by Charpentier et al, Wang et al, and Pareek et al, [13][14][15] who showed a significant reduction in FBS and PPBS (P < 0.001) from baseline than either glimepiride or metformin alone. The results of the present study coincide with these studies where FBS and PPBS decreased significantly (P < 0.01) from baseline to 12 weeks (P < 0.001).…”
Section: Discussionsupporting
confidence: 71%
“…[16][17][18][19] A 16weeks of combination therapy of metformin and teneligliptin by Kim MK et al reported similar significant decrease of FPS and HBA1c in their study. 20 So also a 12weeks study by Kadowaki T et al of glimepiride and teneligliptin combination found effective reduction in FPS, PPS and HBA1c and reduction in HBA1c was maintained even at 52weeks.…”
supporting
confidence: 58%
“…The improvements in glycaemic parameters with glimepiride and metformin were similar, while combination produced a lower degree of reduction with respect to the change in FBG [26,27,28]. The previous studies approved that glimepiride increases insulin sensitivity at peripheral target sites and improve glycemic control in newly diagnosed diabetic subjects, The extrapancreatic effects of glimepiride made its combination with metformin more effective in improving glycemic control by reducing glucose level [29,30].…”
Section: Discussionmentioning
confidence: 99%